2021
DOI: 10.5539/ies.v14n4p83
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Job Burnout Among the Faculty Members of the Private Jordanian Universities in Jordan and the Effect of Gender and Experience Variables on It

Abstract: This study aimed to reveal the level of burnout among the faculty members in private universities in Jordan and the effect of gender and experience variables on it. The researchers used the descriptive analytical method. The study was applied to a random sample of (203) faculty members, who were chosen through a comprehensive survey method, with (169) males and (34) females. A job burnout questionnaire was developed, and its validity and reliability were verified. The results of the study showed that the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Studies showed growing evidence that educators are experiencing high levels of stress (Agai-Demjaha et al, 2015;Kavita & Hassan, 2018;Wettstein et al, 2021). University faculty members experience stress levels incomparable to any other employed group of individuals (Al-Shoqran et al, 2021). Faculty stress was defined by Gmelch and Colleagues as the faculty member's expectation of inability to respond appropriately to a perceived demand, associated with the anticipation of negative consequences due to the insufficient response to work demands (Gmelch et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed growing evidence that educators are experiencing high levels of stress (Agai-Demjaha et al, 2015;Kavita & Hassan, 2018;Wettstein et al, 2021). University faculty members experience stress levels incomparable to any other employed group of individuals (Al-Shoqran et al, 2021). Faculty stress was defined by Gmelch and Colleagues as the faculty member's expectation of inability to respond appropriately to a perceived demand, associated with the anticipation of negative consequences due to the insufficient response to work demands (Gmelch et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the prevalence of SC significantly moderates the stress and performance relationships. Al-Shoqran & Alfandi et al, (2021) performed a study aimed to reveal the level of burnout among the faculty members in private universities in Jordan and the effect of gender and experience variables on it. The study applied a random sample of (203) faculty members, who were chosen through a comprehensive survey method, with (169) males and (34) females.…”
Section: Related Studiesmentioning
confidence: 99%
“…Pearson R product moment correlation degree of relationship home orders put in place during the COVID 19 pandemic create more stress and result in more burnout Al-Shoqran & Alfandi et al, (2021). which they found out the there was a high level of job burnout among the faculty members in private universities in Jordan.…”
mentioning
confidence: 99%